Rantai Pasar Komoditas Pertanian dan Dampaknya Terhadap Kegiatan Perdagangan Komoditas Pertanian Pasar Projo - Erwin Kharisma (Jurnal Wilayah dan Lingkungan, 2014)
Subdistrict Ambarawa as a small town in Central Java is a city that has the potential in the domestic and regional services. Projo market located in downtown Ambarawa is one of the largest traditional market in Semarang Regency. Projo market is a market first that held a special morning vegetable market. Intensive activity often cause traffic jams in front of the Market Projo passed by the national road-Jogjakart Semarang. Ambarawa position is located in the middle of agricultural areas have specialized functions makes Ambarawa make Ambarawa be the exit for agricultural commodities. To find the perpetrator, the location, flow and value-added agricultural commodities in the  market  Projo,  it  is  necessary  to  review  how  the  chain  of  agricultural  commodity  markets  in  the  Market Projo.Market chain analysis will address how the role of Market Projo Ambarawa particularly in the area of the system especially agricultural commodities. From the analysis of the market chain will be known to impact the flow Projo Market chain of agricultural commodities trading activities. Is the impact of the market chain with trading activities have positive and negative for the traders in the Market Projo. This study aims to determine the condition of the agricultural commodity market chain and its relation to the activities of trade in agricultural commodities in the market Projo,   Ambarawa. This   research   approach   is   qualitative   penedekatan  with   descriptive   statistical   analysis techniques. Under the conditions of the market chain will be described the relationship between market chain of agricultural commodities trading activities Projo Market. The results of the analysis it is associated chain actors vegetables and fruits were not only from local actors, but also there are actors nonlocal located near the center producing commodities, such as the perpetrator of farmers and gatherers. While the majority of local actors are actors who sell at the Market Projo such as market traders and retailers. With the presence of nonlocal actors illustrates that commodity in a commodity market Projo nonlocal. Nonlocal vegetables are from Sub Getasan and District Ngablak. Then for for commodities originating from the center of fruit like Batu in  East Java, Malang, Banyuwangi, and Kediri, while for centers such as Magelang, Central Java and Kebumen.For the analysis of the chain, most players in this industry sector is taking the basic ingredients of vegetables and fruits to be processed into other forms, such as food, vegetables, fruit soups, fruit ice. The perpetrator was a perpetrator of restaurants and pkl.For added value, some local actors such as market traders, retailers, and collectors get the added value is large enough compared to other actors of vegetables, local fruits, and fruit imports. Only farmers who obtain the greatest added value of vegetables, fruit for local and imported commodities of local actors such as collectors and market traders get the most added value than nonlocal actors involved. From the above descriptions can be drawn with the impact of the market chain of agricultural commodities trading activities in the Projo Market terfasilitasinya local merchants to sell at the market and value-added Projo received from local traders is quite big compared to nonlocal actors commodity chain of vegetables and fruits. With local traders in the Market terfasilitasinya Projo, it is necessary to the arrangement and the addition of market capacity because the capacity exceeds the capacity of market traders, especially the morning market. Projo market as needed to absorb the local market traders and local people's income will rise gradually to Market Projo can benefit the surrounding community.